Synthesis and Antimicrobial Assessment of Fe3+ Inclusion Complex of p-tert-Butylcalix[4]arene Diamide Derivative - Anwar Ali Chandio; Ayaz Ali Memon; Shahabuddin Memon; Fakhar N. Memon; Qadeer Khan Panhwar; Fatih Durmaz; Shafi Muhammad Nizamani; Nazir Ahmed Brohi (Journal of Chemistry, 2019)
Present study deals with the synthesis of the p-tert-butylcalix[4]arene diamide derivative as ligand (L) and its Fe3+ complex, followed by its characterization using TLC and FT-IR, while UV-Vis and Job’s plot study were performed for complex formation. Antimicrobial activity of the derivative (L) and its metal complex was carried out by the disc diffusion method against bacteria (Escherichia coli and Staphylococcus albus) and fungi (R. stolonifer). Different concentrations of the derivative (L) (6, 3, 1.5, 0.75, and 0.37 μg/mL) and its Fe3+ complex were prepared, and Mueller–Hinton agar was used as the medium for the growth of microorganisms. Six successive dilutions of the derivative (L) and Fe3+ complex were used against microorganisms. Two successive dilutions (6 and 3 μg/mL) of the derivative (L) showed antibacterial action against both Gram-positive and Gram-negative bacteria. In addition, three successive dilutions (6, 3, and 1.5 μg/mL) of the derivative (L) showed antifungal activity. However, all of six dilutions of the Fe3+ complex showed antimicrobial activity. Derivative (L) showed 3 and 1.5 μg/mL minimum inhibitory concentrations (MIC) against bacteria and fungi, respectively. On the contrary, its Fe3+ complex showed 0.37 μg/mL value of MIC against bacteria and fungi. Hence, Fe3+ complex of the derivative (L) was found to be a more effective antimicrobial agent against selected bacteria and fungi than the diamide derivative (L).